Execução penal e transexualidade - Nucci, Amanda Ferreira de Souza (2020)
The present study will analyze the criminal execution in Brazil, with a special focus on the prison system and the imprisonment of transgender population in Brazil. This master's dissertation aims to give visibility to the transgender population, a diversity group of people who choose not to identify themselves with sex assignment (e.g. transsexual or transvestite). Therefore, this study will analyze which changes should be made in the criminal system with focus on the imprisonment of transgender population, in the light of constitutionals principles, especially the dignity of the human person. For this purpose, the study will demonstrate that the reality of the prison system to the transgender population is even harder than for regular prisoners, since this diversity group is more vulnerable, therefore more exposed to psychological and physical violence. Thus, notwithstanding they have a sex assignments, imprison them with the gender they do not identify themselves consists in clear violation of human dignity. Thus, on the assumption that it is a Government duty to aim for dignity conditions for those sentenced to prison and to ensure the respect for human rights, the present dissertation will analyze the overview of Brazilian prison system and the main challenges faced by the transgender population, in order to propose changes in the Brazilian law as well as opening a door for dialogue on this controversy thematic